(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the inclusion of porcine mucosa hydrolysate (PMH) as a flavor stimulant in diets for juvenile tilapia. For this, 12 juvenile tilapia were used, distributed in 12 aquariums, where video recordings were performed to obtain data on attractiveness and palatability: (a) time of capture of the first pellet; (b) rejection of the pellets by the tilapia; (c) approach without ingestion; (d) percentage of ingestion; (e) time taken for the tilapia to consume all the pellets. Six treatments were evaluated in comparison with the control, namely without inclusion of PMH and from one to five percent of inclusion of PMH. The treatment with 1% inclusion presented the highest intake of pellets and, for the other variables, no differences were observed between the evaluated treatments, however, compared to the control, there was a greater decrease in the consumption of the treatment with 3% inclusion. Thus, the inclusion of 1% of PMH is suggested to improve the palatability of the ration offered.